Radiofrequency ablation is a valid treatment option for lung metastases: experience in 566 patients with 1037 metastases. (16th February 2015) - de Baère, T.; Aupérin, A.; Deschamps, F.; Chevallier, P.; Gaubert, Y.; Boige, V.; Fonck, M.; Escudier, B.; Palussiére, J.
Abstract : Radiofrequency of lung metastases below 4 cm, demonstrated an overall survival of 62 months, associated with a 4-year local efficacy of 89%. Repeatability of the technique allows a 4-year lung disease control rate of 44.1%, with patient retreated safely up to four times. Radiofrequency is an option for treatment of small size lung metastases, namely the ones below 2 to 3 cm in diameter. Abstract : Background: Minimal invasive methods are needed as an alternative to surgery for treatment of lung metastases. Patients and methods: The prospective database of two cancer centers including all consecutive patients treated with radiofrequency ablation (RFA) for lung metastasis over 8 years was reviewed. RFA was carried out under general anesthesia, with computed tomography guidance using a 15-gauge multitined expandable electrodes RF needle. Results: Five hundred sixty-six patients including 290 men (51%), 62.7 ± 13.2 years old with primary tumor to the colon (34%), rectum (18%), kidney (12%), soft tissue (9%) and miscellaneous (27%) received 642 RFA for 1037 lung metastases. Fifty-three percent of patients had 1 metastasis, 25% had 2, 14% had 3, 5% had 4 and 4% had 5–8. Metastases were unilateral (75%), or bilateral (25%). The median diameter [extremes] of metastases was 15 mm (4–70). Twenty-two percent of patients had extrapulmonary disease amenable to local therapy including 49 liver, 16 bone and 60 miscellaneous metastases. Median follow-up was 35.5 months. Median overall survival (OS) was 62 months. Four-year local efficacy was 89%. Four-year lung disease control rate was 44.1%, with patient retreated safely up to four times. Primary origin, disease-free interval, size and number of metastases were associated with OS in multivariate analysis. Progression at RFA site was associated with poor OS [ P = 0.011, hazard ratio (HR): 1.69 (95% confidence interval 1.13–2.54)]. In the 293 colorectal cancer metastases, size >2 cm (HR = 2.10, P = 0.0027) and a number of metastases ≥3 (HR = 1.86, P = 0.011) remained significantly associated with OS. A prognostic score made of three groups based on the four above-mentioned prognostic factors demonstrated 3-year OS rates of respectively 82.2%, 69.5% and 53.6% (log-rank test, P ≤ 0.0001) among the three groups in the overall population, and of 81.3%, 72.8% and 57.9% (log-rank test, P = 0.005) in the colorectal cancer patients. Conclusion: Radiofrequency is an option for treatment of small size lung metastases, namely the ones below 2–3 cm.